2007
DOI: 10.1002/jnr.21193
|View full text |Cite
|
Sign up to set email alerts
|

Functional imaging of focal brain activation in conscious rats: Impact of [14C]glucose metabolite spreading and release

Abstract: Labeled glucose and its analogs are widely used in imaging and metabolic studies of brain function, astrocyte-neuron interactions, and neurotransmission. Metabolite shuttling among astrocytes and neurons is essential for cell-cell transfer of neurotransmitter precursors and supply and elimination of energy metabolites, but dispersion and release of labeled compounds from activated tissue would reduce signal registration in metabolic labeling studies, causing underestimation of focal functional activation. Proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 40 publications
4
67
0
Order By: Relevance
“…The stability of 2-DG in the brain tissue, however, is less than previously assumed [30], since it has been shown that 10 min after the injection 2-DG is lost from the brain at a significant rate [11,12]. In any case, the direct comparison of metabolic rates assessed by the 2-DG and 14 C-glucose consumption revealed close correspondence between the two methods for many brain regions [9,10], and 2-DG appears to be a more sensitive marker of regional functional activation after sensory stimulation compared to 14 Cglucose [7][8][9]. Furthermore, the use of 2-DG enabled us to compare our results with previous reports [26,30,35].…”
Section: Experimental Protocol and Data Acquisitionmentioning
confidence: 70%
“…The stability of 2-DG in the brain tissue, however, is less than previously assumed [30], since it has been shown that 10 min after the injection 2-DG is lost from the brain at a significant rate [11,12]. In any case, the direct comparison of metabolic rates assessed by the 2-DG and 14 C-glucose consumption revealed close correspondence between the two methods for many brain regions [9,10], and 2-DG appears to be a more sensitive marker of regional functional activation after sensory stimulation compared to 14 Cglucose [7][8][9]. Furthermore, the use of 2-DG enabled us to compare our results with previous reports [26,30,35].…”
Section: Experimental Protocol and Data Acquisitionmentioning
confidence: 70%
“…Given the role of gap junctions in the buffering of ions, long-range signaling, and exchange of small molecules in astroglial networks (Theis et al, 2005;Scemes and Giaume, 2006;Wallraff et al, 2006;Cruz et al, 2007), astroglial GJCs may play an important role in allowing information processing and integration from a large number of neurons, in providing metabolites to remote sites during high neuronal demand, and in buffering ion or neurotransmitter concentrations . In particular, owing to the proximity of astrocyte gap junctions and neuronal synapses, the concept of the tripartite synapse was initiated (Araque et al, 1999;Perea et al, 2009) and astrocytic networks, thanks to their permeability to Ca 2 + and the potential gliotransmitters such as glutamate, could coordinate the activity of local groups of synapses .…”
Section: Discussionmentioning
confidence: 99%
“…Since each astrocyte can contact over 100,000 synapses (Bushong et al, 2002) and enwrap 4 to 8 neuronal somata (Halassa et al, 2007), the demand on one astrocyte for energy metabolite supply might be overwhelming. Thus, by increasing the effective volume of the intracellular compartment (De Pina-Benabou et al, 2001) and allowing glucose/lactate trafficking towards areas of high neuronal activity (Ball et al, 2007; Cruz et al, 2007; Rouach et al, 2008; Gandhi et al, 2009), gap junctional communication between astrocytes could provide better metabolic support to neurons than could be achieved by individual uncoupled astrocytes.…”
Section: Discussionmentioning
confidence: 99%